The Effect of Solvent Variations on the Phytochemical Profile of Java Chime Fruit Extract (Piper Retrofractum Vahl) With Ultrasonic Method - Hose (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2025)
Javanese chilies are known to contain secondary metabolite compounds in extracts using 96% ethanol, ethyl acetate and n-hexane as solvents. The aim of the research was to determine the secondary metabolite compounds contained in Javanese chili extract using 96% ethanol, ethyl acetate and n-hexane as solvents. The research was conducted in the Pharmacy laboratory of the Islamic University of Madura. The extraction method used is the ultrasonic method using 3 types of solvents, namely 96% ethanol, ethyl acetate, n-hexane. Qualitative testing uses the Phytochemical screening method to determine the content of secondary metabolite compounds such as alkaloids, saponins, flavonoids, tannins and steroids. The research results showed that qualitative testing using the phytochemical screening method with different solvents showed that the extract using 96% ethanol solvent contained secondary metabolite compounds of alkaloids, tannins, saponins and steroids. Extracts with ethyl acetate solvent contain secondary metabolite compounds of alkaloids, tannins and saponins. The extract with n-hexane solvent only contains secondary steroid metabolite compounds. The conclusion of this study shows that different polar properties of the solvent can influence the content of secondary metabolite compounds found in Javanese chili extracts using a phytochemical screening test.